Monilinia laxa brown rot of stone fruit in the Cape Province of South Africa and the importance of latent infections - Schlagbauer, Helen E (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. Agric.) -- University of Stellenbosch, 1987.